2010
DOI: 10.1371/journal.pone.0010927
|View full text |Cite|
|
Sign up to set email alerts
|

Within- and Among-Population Variation in Chytridiomycosis-Induced Mortality in the Toad Alytes obstetricans

Abstract: BackgroundChytridiomycosis is a fungal disease linked to local and global extinctions of amphibians. Susceptibility to chytridiomycosis varies greatly between amphibian species, but little is known about between- and within-population variability. However, this kind of variability is the basis for the evolution of tolerance and resistance evolution to disease.Methodology/Principal FindingsIn a common garden experiment, we measured mortality after metamorphosis of Alytes obstetricans naturally infected with Bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 52 publications
(75 reference statements)
4
95
0
Order By: Relevance
“…This is the first report of chytridiomycosis-associated mortalities of E. coqui in the wild, despite 10 yr of continuous Bd monitoring of a declining population. Our observations support the idea that in species for which mass mortalities are not observed and there is evidence for lability in host defenses, Bd may act as a cryptic driver of population dynamics (Tobler and Schmidt, 2010). Our findings highlight the need for more longitudinal studies to assess the threat of Bd on the survival and fitness of persisting amphibian populations.…”
supporting
confidence: 81%
“…This is the first report of chytridiomycosis-associated mortalities of E. coqui in the wild, despite 10 yr of continuous Bd monitoring of a declining population. Our observations support the idea that in species for which mass mortalities are not observed and there is evidence for lability in host defenses, Bd may act as a cryptic driver of population dynamics (Tobler and Schmidt, 2010). Our findings highlight the need for more longitudinal studies to assess the threat of Bd on the survival and fitness of persisting amphibian populations.…”
supporting
confidence: 81%
“…However, that one adult frog died with mild signs of chytridiomycosis in this study suggests that the ability to clear infection varies among individuals (Tobler and Schmidt 2010). Analysis of capture-markrecapture data showed that the proportion of recaptured adult frogs was lower for infected adult coquis than for uninfected frogs in the Palo Colorado Forest of eastern Puerto Rico .…”
Section: Discussionmentioning
confidence: 55%
“…Tadpoles of some species often show markedly lower susceptibility than postmetamorphic animals (Rachowicz and Vredenburg 2004;Tobler and Schmidt 2010), presumably because keratinized tissue is restricted to mouthparts in tadpoles (Berger et al 1998). In contrast, tadpoles of other species show reduced survival from infection, particularly when exposed to high doses of Bd (Blaustein et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the study by Bielby et al (2009) is the first evidence in Europe of significant adult anuran mortality linked with possible declines. Other published studies of lethal chytridiomycosis in European anurans report mortality primarily in near-or recently metamorphosed juveniles (Bosch et al 2001;Bosch & Martínez-Solano 2006;Garner et al 2009b;Pasmans et al 2010;Tobler & Schmidt 2010;Walker et al 2010). Mortality and decline of Salamandra salamandra involved some adult mortality, but even in this case the majority of dead animals observed by Bosch & Martínez-Solano (2006) were near-or recently metamorphosed juveniles.…”
Section: Introductionmentioning
confidence: 92%
“…The first record in captivity describes infection of imported, wildcollected animals as well as captive-reared amphibians, both sampled in 1999 in Germany and Belgium (Mutschmann et al 2000). Since then our knowledge regarding the distribution of infection in Europe and European hosts has increased substantially (Garner et al 2005;Bosch & Martínez-Solano 2006;Garner et al 2006;Bosch et al 2007;Bovero et al 2008b;Walker et al 2008;Bielby et al 2009;Garner et al 2009b;Pasmans et al 2010;Tobler & Schmidt 2010;Walker et al 2010;Ohst et al 2011;Sztatecsny & Glaser 2011). Bd was detected for the first time in Italy in 2000 (as reported in ), but little is known regarding the impact of Bd on Italy's highly diverse amphibian fauna.…”
Section: Introductionmentioning
confidence: 99%